Accelerated biological aging and risk of inflammatory bowel disease: A prospective study from 401,013 participants - Baolong Cao; Xiaoke Zhao; Zhixi Lu; Hongmei Zhang (The Journal of Nutrition, Health and Aging)
Objectives: Relationship between biological aging and inflammatory bowel disease (IBD) remains unclear. We aimed to explore the associations of biological age and genetic predisposition with IBD and the predictive ability. Methods: Biological age and genetic predisposition were measured by PhenoAge and the polygenic risk score (PRS), respectively. The hazard ratio (HR) and 95% confidence interval (CI) of PhenoAge and combined PRS for Crohn’s disease (CD) and ulcerative colitis (UC) were evaluated by Cox proportional hazards models. Additive interactions were examined to evaluate the joint effect. C statistic was employed to assess the predictive ability. Results: During the follow-up period of 5,320,311 person-years of 401,013 participants, 2467 patients with UC and 1262 patients with CD were observed. PhenoAge showed a significant association with an increased risk of incident IBD. Each standard deviation of PhenoAge acceleration correlated with a 38% (95% CI: 34%–41%), 35% (95% CI: 30%–38%), and 46% (95% CI: 41%–51%) increased risk of IBD, UC, and CD, respectively. Joint effects and additive interactions were noted between PhenoAge and the PRS. Individuals with a high PRS and the highest PhenoAge acceleration had the highest risk for UC (HR: 9.16, 95% CI: 7.08–11.85) and CD (7.72, 6.05–9.86), respectively. Incorporating PhenoAge and the PRS could enhance the accuracy of predicting IBD, with a highest C statistic of 0.71 for UC and 0.72 for CD. Conclusion: Accelerated biological aging is associated with an increased risk of IBD, particularly in individuals with high genetic predisposition. Identifying individuals with accelerated biological aging has significant implications for reducing IBD risk.